2019
DOI: 10.1177/1947603519894732
|View full text |Cite
|
Sign up to set email alerts
|

HemiCAP Knee Implants: Mid- to Long-Term Results

Abstract: Purpose The aim of the study was to investigate the long-term outcomes of the Focal Femoral Condyle Resurfacing Prosthesis (HemiCAP) using clinical and radiographic assessments, and to evaluate the revision and survival rates. Methods Clinical evaluation was performed in those not revised and was able to participate. This was a prospective single-center cohort study of HemiCAP patients with 7 to 10 years of clinical and radiographic follow-up. The clinical examination included the Knee Society Score (KSS) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 29 publications
3
12
0
Order By: Relevance
“…This suggests that if symptomatic degenerative cartilage lesions are of limited size rather than an element of generalized OA, then resurfacing implant treatment can provide long-term improvement. The results of 70% not revised to knee arthroplasty after mean 9 years, indicate that resurfacing implants may limit the need for a UKA or TKA in elderly patients (> 65 years old) with symptomatic cartilage lesions or early degenerative knee pathologies [8,11,[15][16][17][18]. Thus far, the present study is the only and largest long-term case series, with 23 femoral resurfacing mini prostheses in elderly knee-patients with clinical and radiographic follow-up up to 11 years, including revision and survival rates.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that if symptomatic degenerative cartilage lesions are of limited size rather than an element of generalized OA, then resurfacing implant treatment can provide long-term improvement. The results of 70% not revised to knee arthroplasty after mean 9 years, indicate that resurfacing implants may limit the need for a UKA or TKA in elderly patients (> 65 years old) with symptomatic cartilage lesions or early degenerative knee pathologies [8,11,[15][16][17][18]. Thus far, the present study is the only and largest long-term case series, with 23 femoral resurfacing mini prostheses in elderly knee-patients with clinical and radiographic follow-up up to 11 years, including revision and survival rates.…”
Section: Discussionmentioning
confidence: 99%
“…Laursen et al . 22 have published a series of studies on HemiCap and UniCap. The authors followed 62 patients with 64 HemiCap prosthesis for 7 to 10 years and found a revision rate of 42%.…”
Section: Discussionmentioning
confidence: 99%
“…The authors followed 62 patients with 64 HemiCap prosthesis for 7 to 10 years and found a revision rate of 42%. 22 Studying the HemiCap Wave for patellofemoral defects, the authors found a revision rate of 28% after 6 years in 18 patients 22 and in 64 patients treated with UniCap (designed for larger defects), the authors found a revision rate of 56%. 23 Laursen et al .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations